1999
DOI: 10.1017/s0007485399000541
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of rice leaffolders (Lepidoptera: Pyralidae) and their natural enemies in irrigated rice in the Philippines

Abstract: Populations of rice leaffolders and their natural enemies were studied in eight crops of irrigated rice in Laguna Province, the Philippines. The rice leaffolder complex consisted of three species: Cnaphalocrocis medinalis (Guenée), Marasmia patnalis Bradley and M. exigua Butler. Leaffolder population dynamics were characterized by an egg peak at maximum tillering and a broad larval peak around booting stage. Peak densities ranged from 0.2 to 2.0 larvae per hill. Most larvae originated from immigrant moths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
(21 reference statements)
3
15
0
Order By: Relevance
“…This finding agrees with a result of a similar study by De Kraker et al (1999), in irrigated rice in the Laguna Province, the Philippines. The same study reported egg parasitism of C. medinalis by Trichogramma to be 0 -27 %.…”
Section: According To Previous Studies Trichogramma Chilonis T Closupporting
confidence: 93%
See 1 more Smart Citation
“…This finding agrees with a result of a similar study by De Kraker et al (1999), in irrigated rice in the Laguna Province, the Philippines. The same study reported egg parasitism of C. medinalis by Trichogramma to be 0 -27 %.…”
Section: According To Previous Studies Trichogramma Chilonis T Closupporting
confidence: 93%
“…This approach requires the identification of locally available egg parasitoids. In some countries, the egg parasitoid guild of RLF has been characterised (De Kraker et al, 1999). In Sri Lanka the larval and pupal parasitoids have been identified (Rajapakse, 1990) This study was conducted with the following objectives.…”
Section: Laboratory Rearing Of Egg Parasitoidsmentioning
confidence: 99%
“…Three coccinellid predators namely, B. suturalis, S. parcesetosum and C. transversalis were observed in mungbean and urdbean during July to September [22]. In the paddy filed, C. longipennis had a minor role in control insect pest [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The method is not suitable for sampling highly mobile flying insects, such as predatory Odonata or larger hymenopterous parasitoids. As with any sampling method, the combination of the blower-vac with other methods, such as sweep net sampling or destructive harvesting of plants, can provide a more complete and balanced assessment of the arthropod community 26 .…”
Section: Discussionmentioning
confidence: 99%